Investigation of the rock mass state in the near-wall part of the quarry and its stability management - Saik, Pavlo; Rysbekov, Kanay; Kassymkanova, Khaini-Kamal; Lozynskyi, Vasyl; Kyrgizbayeva, Guldana; Moldabayev, Serik; Babets, Dmytro; Salkynov, Arnat (Frontiers in Earth Science, 2024)
The research is aimed to identify the vulnerable areas of quarry slopes through the creation of a stress-strain state model for the rock mass at the Vostochny quarry, East Saryoba field of the Zhilandy Group of cupriferous sandstones, as well as their subsequent strengthening. The research is based on the development of a database containing information on mining-geological, geophysical, geodetic and aerospace surveys. The authors of the research use modern geodetic, aerospace and geophysical technologies for scientifically based predicting of technogenic disasters and the rock mass stress-strain state modeling to ensure safe and optimal mining of fields in difficult mininggeological conditions. The results obtained show that the strengthening of weakened quarry slopes based on the rock mass stress-strain state modeling contributes to the scientific-practical profitability of field mining and provides safe mining in difficult mining-geological conditions. Novelty is in the scientific substantiation of the method for strengthening quarry slopes, which is based on the rock mass stress-strain state modeling. The research is of great practical importance, as the rock mass stress-strain state modeling increases the reliability of predicting the rock mass state during its mining. Strengthening of quarry slopes using the proposed method reduces risks and increases safety and economic efficiency of mining the solid mineral deposits in difficult mining-geological conditions.